Sustainable tourism and green space: exploring how green spaces and natural attractions contribute to local tourism economies and revenue generation in Gauteng province - Enioluwa Jonathan Ijatuyi; Kowiyou Yessoufou; Hosea Olayiwola Patrick (Discover Sustainability)
Abstract Green spaces and natural attractions are critical assets in promoting sustainable tourism, particularly in ecologically diverse regions such as South Africa. This systematic scoping review explores how green spaces and natural attractions contribute to local tourism economies and revenue generation, with a focus on a specific South African province. By examining the roles of parks, nature reserves, and other green areas, this review highlights the economic benefits of green spaces for tourism, job creation, conservation efforts, and local community engagement. Using a structured approach where 624 secondary sources were systematically reviewed and streamline to 134 for a thematic content analysis, the study assessed how sustainable tourism practices enhanced economic benefits while preserving natural resources. By focusing on a specific province, the research provided insights into the interplay between environmental conservation and economic development within the tourism sector. The study’s finding identifies key challenges and strategies for maximizing the economic potential of sustainable tourism in South Africa. It highlights the challenges in leveraging green spaces for sustainable economic growth and proposes strategies to enhance the economic benefits of these areas. It recommended that by addressing the challenges through comprehensive strategies and collaborative efforts, stakeholders can create a thriving green tourism sector that benefits both the environment and local economies.